Serum kisspeptin levels along reproductive period in women: is it a marker for aging?. (4th March 2022) - Erel, C. Tamer; Ozcivit, Ipek Betul; Inan, Deniz; Mut, Aysegül; Karakus Hatipoglu, Burçin; Konukoglu, Dildar
Abstract: Objective: To demonstrate the change in serum kisspeptin levels during the reproductive period in healthy women and to investigate the relationship with other reproductive hormones. Methods: One hundred thirty-one healthy women with normal menstrual history were included and serum kisspeptin, follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid-stimulating hormone (TSH), estradiol (E2 ), and anti-Müllerian hormone (AMH) levels were determined on cycle day 3. The data were analyzed in 5-year age groups. Results: Serum kisspeptin levels of all women were found to be significantly and negatively correlated with age ( r = −0.458). The kisspeptin levels were the highest in the group of women aged between 20 and 24 years compared to other age groups above 25 years ( p  < .01, p  < .001, p  < .0005, p  < .0005). There was not any significant correlation between serum kisspeptin levels and AMH, FSH, LH, TSH, E2, and body-mass index (BMI), respectively. The Scatter and Violin plots showed that most of the women over 35 years of age had serum kisspeptin levels under the level of 500 pg/ml. The kisspeptin levels of women over 35 years of age clustered closely as opposed to the kisspeptin levels of those below the age of 35, which were scattered. The median serum kisspeptin levels were found to be high in women below the age of 35 ( p  < .0005). Conclusion: In healthy women, serum kisspeptin level is the highest in the group of women aged between 20 and 24 years and declines with age. It tends to be below the level of 500 pg/ml in women over the age of 35.